Study of the tensile behavior of AISI type 316 stainless steel using acoustic emission and infrared thermography techniques - Thodamrakandy Haneef; Barid Baran Lahiri; Subramaniam Bagavathiappan; Chandan Kumar Mukhopadhyay; John Philip; Bhagi Purna Chandra Rao; Tamanna Jayakumar (Journal of Materials Research and Technology, 2015)
Acoustic emission (AE) and infrared thermography technique (IRT) have been used to study the tensile behavior of AISI type 316 stainless steel. Strain rates of tensile testing were varied from 1.4 × 10−3 s−1 to 1.4 × 10−2 s−1. AE root mean square voltage increases with increase in strain rate due to the increase in source activation. Dominant frequency of the AE signals generated during different regions of tensile deformation has also been used to compare the results for different strain rates. The dominant frequency increases from elastic region to around 590 kHz during work hardening and 710 kHz around ultimate tensile strength (UTS) for all the strain rates. Temperature changes during different regions of deformation are monitored using infrared thermography. The temperature rise in the work hardening region is found to approximately increase linearly with time and from the slopes of the linear regression analyses the rate of temperature rise in the work-hardening region is obtained which is found to be very sensitive to strain rates. From the experimental results an empirical equation that relates the rate of temperature increase with strain rate and thermal hardening coefficient is obtained. The correlation between the variation of AE dominant frequency and temperature rise during different deformation regions provided better insight into the tensile behavior of AISI type 316 SS for different strain rates.